2017
DOI: 10.1080/10942912.2017.1311344
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles and sensory characteristics of yogurt manufactured by incorporating basil (Ocimum basilicum L.)

Abstract: Purple basil was used as powder or water extract forms in the manufacture of yogurt for possible contribution on its taste and flavour of yogurt. The volatiles were extracted by solid-phase micro-extraction and then determined by gas chromatography-mass spectrometry (GC-MS) system. Effects of the addition of purple basil as powder or water extract form on the volatile composition and sensory characteristics during 3 weeks of storage at 4°C were evaluated. Forty-nine compounds were identified in the volatile co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
(39 reference statements)
2
10
0
Order By: Relevance
“…Acetic acid is an important compound in yogurts and was found in concentrations similar to other studies [41]. Other acids that were detected and are frequently found in dairy products were butanoic, hexanoic, octanoic, nonanoic, and decanoic acids [16,24,26,40]. The use of L. casei resulted in significantly ( p < 0.05) higher concentrations of butanoic, hexanoic, and octanoic acids, while immobilized cells resulted in significantly higher concentrations of acetic and decanoic acids.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Acetic acid is an important compound in yogurts and was found in concentrations similar to other studies [41]. Other acids that were detected and are frequently found in dairy products were butanoic, hexanoic, octanoic, nonanoic, and decanoic acids [16,24,26,40]. The use of L. casei resulted in significantly ( p < 0.05) higher concentrations of butanoic, hexanoic, and octanoic acids, while immobilized cells resulted in significantly higher concentrations of acetic and decanoic acids.…”
Section: Resultssupporting
confidence: 68%
“…However, research on the development of novel yogurt-based products is increased in recent years in order to fulfill two main demands of consumers. Firstly, the request for more healthy foods has led to the development of novel functional dairy products with potential health benefits like probiotic yogurts [24] and, secondly, the increasing popularity of yogurts with new flavors has resulted in the development of novel yogurts with different sources of fruit flavorings [25,26]. In this study, both requirements were fulfilled by using immobilized L. casei ATCC 393 cells on apple pieces or casein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decrease in the acetaldehyde and ethanol levels in yogurt butter samples coincided with an increasing acetic acid level (Tables 3, 4 and 5). Gürkan and Hayaloglu (2017) also found that the amount of acetaldehyde decreased in yoghurt during storage. Some authors reported that the conversion of acetaldehyde, acetic acid and ethanol was correlated with water activity and pH (Liu et al, 1997).…”
Section: Aldehydes and Ketonesmentioning
confidence: 80%
“…Therefore, by choosing an appropriate drying method and practical conditions, the good quality product can be obtainable (Hamrouni-Sallami et al, 2013). Several researchers studied on drying of Ocimum basilicum such as tray dryer (Kadam, Goyal, & Gupta, 2011), microwave dryer (Pirbalouti, Mahdad, & Craker, 2013) and vacuum microwave dryer (Yousif, Scaman, Durance, & Girard, 1999), freeze dryer (Díaz-Maroto et al, 2004) and sunlight (Kavak-Akpınar, 2006) and shade (Gurkan & Hayaloglu, 2017). Spices including important amount of microorganisms, due to high microbial load caused by inadequate hygiene conditions during growing, crop, processing, and storage increase count of intoxications (Buckenhiiskes & Rendlen, 2004).…”
Section: Introductionmentioning
confidence: 99%